IMPOLITENESS: AN ANALYSIS OF COMMUNICATION VIA SMS - Ike Revita (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Impolitenes is a kind of attitude that is regarded breaking the rule and the norm in social life. In communication, impoliteness is really avoided since this may threaten one’s face and bring about the miscommunication. Once miscommunication occurs, the disharmonity may come up. Thus, being impolite must be denied. However, impoliteness sometimes can not be prevented in communication, specifically when it is done via short message service (SMS). This writing is aimed at describing the phenomena of being impolite in communication via SMS. The objective of the writing is identify the motivation of being impolite in communication via SMS. The data are any SMS sent by English Department Students Andalas University to some lecturers. The data are collected by observational method and anlyzed by pragmatic and referential identity method. The result of analysis is presented narratively and descriptively. Having related to the concept of impolitness proposed by Culpeper (1995) and Oktavianus and Revita (2013), it is found that there are several motivations bringing about the students being impolite in communication via SMS. They are (1) lack of pragmalinguistic competence and (2) sociopragmatic considerations. Keywords: Impoliteness, Pragmalinguistic, SMS, Sociopragmatic